Energetic capability of a photovoltaic thermal collector in the façade. Issue 5 (22nd October 2018) - Weller, Bernhard; Popp, Christian; Seeger, Julia; Scheuring, Leonie
ABSTRACT: Photovoltaic thermal (PVT) collectors result from the fusion of Photovoltaic (PV) modules and solar thermal collectors. By combining both technologies, PVT systems can generate electricity and thermal energy at the same time. This leads to a higher utilization of the solar irradiation, regarding the required space. So far, the yearly installed PVT area is marginal compared to the installed PV area. Thus, in the field of building integration there are only sporadic PVT roof systems and almost no PVT façade systems detectable. In order to determine the energetic capability and to estimate the potential of façade integrated PVT systems, thermal simulations were carried out as a basis for this article. These simulations give information about important constructive and plant‐specific boundary conditions of the analyzed PVT façade system and create the basis for the development of a PVT façade collector. In a second step, a façade integrated PVT collector will be constructed and monitored at an outdoor exposure test rig at the Dresden University of Technology. By comparing the measured data to the simulated data, a review and validation of the simulation is intended.